PROGRAMA RESTART: EDUCAÇÃO E TRATAMENTO PSICOLÓGICO DA DEPENDÊNCIA TECNOLÓGICA DE JOVENS - Neu, Karolina Ida Martins; Tasca, Paula Cristina (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This article is the result of an Extension project applied in the west of Santa Catarina in theyears 2018, 2019 and 2020, where it aims to educate and treat technological dependence inyoung people.The ReStart Program featured lectures at schools, preparation of a portfolio anda reflective group with high school teenagers. Lectures were held onTechnological Dependence in 04 High Schools in the morning and afternoon shifts,covering the audience of students and teachers. Through the portfolio was published throughof social networks, videos, articles, research samples and images, in order to bring reflectionto the public, with an easy-to-understand language and visualization. In the group with theteenagers, issues related to becoming a subject in relationships were addressed.real/virtual, addressing the themes and practices developed, as well as discussing theresults and perceptions about the group. It is concluded that through the extension projectyou can have a greater understanding of the relationship of teenagers with technology,enabling spaces for reflection on technology and topics such as use and abuse, drugs,bullying and relationships.